Temporal Changes in Gene Expression Profile during Mature Adipocyte Dedifferentiation. (19th March 2017) - Côté, Julie Anne; Guénard, Frédéric; Lessard, Julie; Lapointe, Marc; Biron, Simon; Vohl, Marie-Claude; Tchernof, André
Abstract : Objective . To characterize changes in gene expression profile during human mature adipocyte dedifferentiation in ceiling culture. Methods . Subcutaneous (SC) and omental (OM) adipose tissue samples were obtained from 4 participants paired for age and BMI. Isolated adipocytes were dedifferentiated in ceiling culture. Gene expression analysis at days 0, 4, 7, and 12 of the cultures was performed using Affymetrix Human Gene 2.0 STvi arrays. Hierarchical clustering according to similarity of expression changes was used to identify overrepresented functions. Results . Four clusters gathered genes with similar expression between day 4 to day 7 but decreasing expression from day 7 to day 12. Most of these genes coded for proteins involved in adipocyte functions ( LIPE, PLIN1, DGAT2, PNPLA2, ADIPOQ, CEBPA, LPL, FABP4, SCD, INSR, and LEP ). Expression of several genes coding for proteins implicated in cellular proliferation and growth or cell cycle increased significantly from day 7 to day 12 ( WNT5A, KITLG, and FGF5 ). Genes coding for extracellular matrix proteins were differentially expressed between days 0, 4, 7, and 12 ( COL1A1, COL1A2, and COL6A3, MMP1, and TGFB1 ). Conclusion . Dedifferentiation is associated with downregulation of transcripts encoding proteins involved in mature adipocyte functions and upregulation of genes involved in matrix remodeling, cellular development, and cell cycle.